Aerogel‐Functionalized Thermoplastic Polyurethane as Waterproof, Breathable Freestanding Films and Coatings for Passive Daytime Radiative Cooling. Issue 20 (27th April 2022) - Shan, Xiameng; Liu, Ling; Wu, Yusi; Yuan, Dengsen; Wang, Jing; Zhang, Chengjiao; Wang, Jin
Abstract: Passive daytime radiative cooling (PDRC) is an emerging sustainable technology that can spontaneously radiate heat to outer space through an atmospheric transparency window to achieve self‐cooling. PDRC has attracted considerable attention and shows great potential for personal thermal management (PTM). However, PDRC polymers are limited to polyethylene, polyvinylidene fluoride, and their derivatives. In this study, a series of polymer films based on thermoplastic polyurethane (TPU) and their composite films with silica aerogels (aerogel‐functionalized TPU (AFTPU)) are prepared using a simple and scalable non‐solvent‐phase‐separation strategy. The TPU and AFTPU films are freestanding, mechanically strong, show high solar reflection up to 94%, and emit strongly in the atmospheric transparency window, thereby achieving subambient cooling of 10.0 and 7.7 °C on a hot summer day for the TPU and AFTPU film (10 wt%), respectively. The AFTPU films can be used as waterproof and moisture permeable coatings for traditional textiles, such as cotton, polyester, and nylon, and the highest temperature drop of 17.6 °C is achieved with respect to pristine nylon fabric, in which both the cooling performance and waterproof properties are highly desirable for the PTM applications. This study opens up a promising route for designing common polymers for highly efficient PDRC. Abstract : Aerogel‐functionalized thermoplastic polyurethane freestanding films and coatings are designed and prepared by a non‐solvent‐phase‐separated strategy for efficient passive daytime radiative cooling. The films are mechanically strong and achieve a subambient cooling of 10.0 °C on a hot day. When used as coatings for traditional textiles, a radiative cooling of 17.6 °C is achieved with respect to pristine nylon fabric.